Block and Lock HIV Cure Strategies to Control the Latent Reservoir - Ahlenstiel, Chantelle L.; Symonds, Geoff; Kent, Stephen J.; Kelleher, Anthony D. (Frontiers in Cellular and Infection Microbiology, 2020)
The HIV latent reservoir represents the major challenge to cure development. Residing in resting CD4+ T cells and myeloid cells at multiple locations in the body, including sanctuary sites such as the brain, the latent reservoir is not eliminated by ART and has the ability to reactivate virus replication to pre-therapy levels when ART is ceased. There are four broad areas of HIV cure research. The only successful cure strategy, thus far, is stem cell transplantation using naturally HIV resistant CCR532 stem cells. A second potential cure approach uses gene editing technology, such as zinc-finger nucleases and CRISPR/Cas9. Another two cure strategies aim to control the HIV reservoir, with polar opposite concepts; The “shock and kill” approach, which aims to “shock” or reactivate the latent virus and then “kill” infected cells via targeted immune responses. Lastly, the “block and lock” approach, which aims to enhance the latent virus state by “blocking” HIV transcription and “locking” the HIV promoter in a deep latent state via epigenetic modifications. “Shock and kill” approaches are a major focus of cure studies, however we predict that the increased specificity of “block and lock” approaches will be required for the successful development of a sustained HIV clinical remission in the absence of ART. This review focuses on the current research of novel “block and lock” approaches being explored to generate an HIV cure via induction of epigenetic silencing. We will also discuss potential future therapeutic delivery and the challenges associated with progressing “block and lock” cure approaches as these move towards clinical trials.